Clinical and biological heterogeneity of multisystem inflammatory syndrome in adults following SARS-CoV-2 infection: a case series - Barth, Kaia E.; Spottiswoode, Natasha; Hurabielle, Charlotte; Subbaraj, Lakshmi; , COMET Consortium; Calfee, Carolyn S.; Matthay, Michael A.; French, Sarah; Connolly, Andrew; Hewitt, Stephen M.; Vannella, Kevin M.; Barnett, Christopher; et al. (Frontiers in Medicine, 2023)
Importance Multisystem inflammatory syndrome in adults (MIS-A) is a poorly understood complication of SARS-CoV-2 infection with significant morbidity and mortality. Objective Identify clinical, immunological, and histopathologic features of MIS-A to improve understanding of the pathophysiology and approach to treatment. Design Three cases of MIS-A following SARS-CoV-2 infection were clinically identified between October 2021 – March 2022 using the U.S. Centers for Disease Control and Prevention diagnostic criteria. Clinical, laboratory, imaging, and tissue data were assessed. Findings All three patients developed acute onset cardiogenic shock and demonstrated elevated inflammatory biomarkers at the time of hospital admission that resolved over time. One case co-occurred with new onset Type 1 diabetes and sepsis. Retrospective analysis of myocardial tissue from one case identified SARS-CoV-2 RNA. All three patients fully recovered with standard of care interventions plus immunomodulatory therapy that included intravenous immunoglobulin, corticosteroids, and in two cases, anakinra. Conclusion MIS-A is a severe post-acute sequela of COVID-19 characterized by systemic elevation of inflammatory biomarkers. In this series of three cases, we find that although clinical courses and co-existent diseases vary, even severe presentations have potential for full recovery with prompt recognition and treatment. In addition to cardiogenic shock, glucose intolerance, unmasking of autoimmune disease, and sepsis can be features of MIS-A, and SARS-CoV-2 myocarditis can lead to a similar clinical syndrome.